Construction of Innovation and Entrepreneurship Education Ecosystem in Higher Vocational Colleges from the Perspective of System Theory. (11th March 2022) - Zheng, Chuanjuan; Sun, Liandong; Guo, Huifang
Abstract : Innovation and entrepreneurship (IAE) education in higher vocational education is mainly to cultivate college students' innovative spirit and ability, and it is an important way to promote economic development. However, the current academic research on the construction of IAE education ecosystem in higher vocational school (HVS) is relatively weak. In order to improve the IAE education ecosystem of HVS and strengthen the innovation of HVS education system, this study systematically discusses and analyzes the system from the four aspects of system boundary, state, power, and movement and further innovates and constructs the IAE education ecosystem of HVS on the basis of university education system, subject cooperation, and mechanism management. The results prove the feasibility of HVS IAE education ecosystem from the perspective of system theory, enhance the cultivation of HVS talents' IAE ability, and are of great significance to promote the comprehensive reform of higher vocational school education system.